Violence Due to Prejudice Against People with Diverse Sexual Orientation or Gender Identity in the Venezuelan Legal-judicial System (2017)
Purpose: Violence based on sexual orientation and/or gender identity constitutes a violation of human rights. Therefore, the purpose of this article is to characterize the legal-judicial aspect of violence against people of diverse gender/sex. Description: Certain individuals face a high level of violence due to prejudice against their sexual orientation and gender identity. This is the case of people of diverse sex/gender such as the community composed of lesbians, gays, bi-, trans- and intersexuals (lgbti). Approach: Violence due to prejudice is a concept that points to an understanding of violence as a social phenomenon, as opposed to violence understood as an isolated event. Human rights are universal, inalienable, indivisible, interconnected and interdependent. Each individual, regardless of their sexual orientation or gender identity, is entitled to the respect, protection, exercise and enjoyment of all fundamental human rights and freedoms. In the Venezuelan legal system, this protection is not provided to people of diverse sex/gender despite the existence of a law that is very succinct. Conclusions: There are still many legal gaps regarding violence due to hate or prejudice against people of diverse sex/gender in Venezuela, despite the national Constitution and other national laws, as well as the obligations of international treaties adopted by the Venezuelan State, which grant certain implicit and explicit protections to this community. Legislative and jurisdictional regulations have not assembled any legal position. The partial reform that was made to the Penal Code in 2005, regarding the provisions on hate crimes resulting from violence due to prejudice, has not been implemented even though there are many reported cases of this type of violence in daily practice.